Pengembangan Manajemen Sumber Daya Manusia Berbasis Kompetensi Guna Meningkatkan Kinerja Pegawai Dan Dosen Polikteknik Perkeretaapian Indonesia - Istiantara, Dedik Tri (Politeknik Perkeretaapian Indonesia Madiun, 2019)
Human resource management is one of the sciences in managing the workforce (HR) to be effective and efficient in helping to realize the goals of an organization. The Indonesian Railroad Polytechnic as one of the higher education institutions formed to prepare superior human resources in the field of railways. The Indonesian Railroad Polytechnic makes various efforts in improving the quality of education quality. The increasingly sharp HR preparation competition has implications for the Indonesian Railways Polytechnic institutional organization to make quality-oriented changes by motivating employees and lecturers to work harder in a professional manner. The hope is that employees will further improve performance in accordance with predetermined standards. However, the reality is that the existing management model has not been able to improve the performance of staff and lecturers. This is evident that based on data obtained from the Head of Personnel in April 2019 that of 150 employees around 25 employees who work are not in accordance with the field of expertise owned, thus providing a significant influence on employee performance results. Besides that, some lecturers are less motivated to do Higher Education Tri Darma, such as community service and research. In this study, researchers wanted to develop a HR management model to improve employee performance. The method used in this research is Research & Development (R&D). The results of research on competency-based HR Management Model can improve the performance of lecturers and staff to be more productive.